Manfaat pojok baca di dalam kelas MI Miftahul Ulum Balearjo - Aghfar, M. Sambuaga (Maliki Interdisciplinary Journal, 2023)
Reading is an activity that involves understanding the reading text and then understanding the content of the text through the voice or heart. Reading is very important for students at school, so MI Miftahul Ulum created a reading corner in the classroom. The reading corner is an effective innovation to introduce students’ interest in reading. The reading corner is a strategically designed corner of the room in the classroom with the aim of attracting students’ attention, captivating students’ reading interest, and encouraging students to read. This study aims to find out what the benefits of the reading corner are at MI Miftahul Ulum Balearjo. This study uses observation and interview methods to find out what are the benefits of the reading corner at MI Miftahul Ulum Balearjo. The benefits of the reading corner at MI Miftahul Ulum are encouraging students to prefer reading activities, bringing books closer to students so that they are more interested in reading, helping the library in introducing a culture of reading, and being part of the learning process by the teacher.